Do Managers’ Affiliation Ties Have a Negative Relationship with Subordinates’ Interfirm Mobility? Evidence from Large U.S. Law Firms - Carnahan, Seth; Rabier, MaryJane; Uribe, Jose (Organization Science, 2022)
We hypothesize that employee mobility between organizations will be lower when the organizations’ managers share affiliation ties. We test this idea by examining interorganizational employee mobility between large corporate law practices. We find that a practice area is less likely to hire attorneys from a rival practice area when the leaders of the two practice areas attended the same law school at the same time, our proxy for the presence of an affiliation tie. The negative relationship is stronger for hiring higher-ranked attorneys, and it is driven by practice leaders from the same law school class. Exploiting appointments of new practice leaders, we find a sharp and immediate decline in interorganizational mobility following an appointment that creates an affiliation tie between the leadership of the practice areas. Although we cannot rule out the possibility that job seekers’ preferences drive the results, we conclude that rival managers’ ties deserve further scrutiny because they might limit the outside employment opportunities of their subordinates.